Potential effects of flaxseed (Linum usitatissimum) in tissue reparative processes: a mini review - Shaban, Sama; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Arief Ichwan, Solachuddin Jauhari (Penerbit AMDI Press, Universiti Sains Malaysia, 2020)
Wounds are inevitable events that can occur daily due to many factors such as; physical, chemical and biological, which can cause tissue, cell and in some events bone damage. The process of wound healing is complicated as it involves many factors; therefore, an effective and safe agent is essential to ensure good healing process. Herbal medicine is considered safe and effective. Flaxseed (Linum usitatissimum) is an effective plant when it comes to wound healing and has been used for decades as a traditional healing agent. The bioactivities of flaxseed extract have been reported to demonstrate many beneficial effects such as antimicrobial, antioxidant and anti-inflammatory effects. It has been shown that flaxseed has positive effects on many types of wounds such as skin wound healing, burns and burn scar healing, bone healing and also has demonstrated positive results in the healing of oral ulceration besides exhibiting anti-bacterial effects in the oral cavity. This review describes the positive effects of flaxseed in multiple types of wound healing. Additionally, it is also aimed to introduce the potential applications of flaxseed in socket healing which involves series of complex changes to both soft and hard tissues in the oral cavity